MISTISISME PEREMPUAN DALAM DIWAN TARJUMAN AL-ASYWAQ KARYA IBNU ARABI - Hasanah, Mir'atul (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2018)
Diwan Tarjuman al-Asywaq is one of the master piece of Ibnu Arabi as known the famous sufic mystic in Islam. A poetry in Diwan Tarjuman al-Asywaq appears controversy in Islam world because this poetry is considered to show the love story of Ibnu Arabi with the girl whom he loves. This study will present meaning of metaphor and symbol in this poetry with hermeneutic analysis of Paul Ricoeur. Hermeneutic Ricoeur will explain objectively meaning in this poetry (sense) and then put this meaning in the real life (reference). The result finds that idea of “little girl” in this poetry is interpretation of “Allah” who has nobleness, purity, beautification, and the high place. “Allah” with his perfection is presented through form of “woman” as formal form in interpretation of “Allah”.